The Role of Extra-Campus Organization in Building "Bela Negara" Character: Case of Cipayung Group of East Java - Sri Wibawani; Anis Rosella Pitaloka; Luluk Ul Magnun; Roiyanatun Mahbubah; Jojok Dwiridotjahyono (Journal of Economics, Business, and Government Challenges, 2020)
This study aims to explore the role of the Extra-Campus Student Organizationsincorporated in the Cipayung Group, namely: Indonesian National StudentMovement (GMNI), Indonesian Islamic Student Movement (PMII), IndonesianStudent Association (HMI), Indonesian Christian Student Movement (GMKI) ),and the Catholic Students Association of the Republic of Indonesia (PMKRI) inraising awareness of the nation defense in East Java. This study uses a qualitativeapproach with data collection techniques in the form of content analysis ofcredible news, in-depth interviews, and focus group discussions (FGD) oninformants or informants selected based on purposive techniques. The dataanalysis technique used is an interactive model, and the data validity test techniqueuses triangulation. The results of this study indicate that the Copying Group interms of regeneration implanted the values of the country's defense throughcompulsory material delivered in activities ranging from member recruitment,primary education and training, and further training. In terms of scientific studiesand issues, the Copying Group often conducts study discussions that also carry thetheme of defending the country. In terms of student actions or movements, thevalues of state defense instilled through efforts to criticize government policiesthat are considered non-Pancasila. Copying Group members also carry outcommunity service which aims to instill in their members that love for themotherland and willingness to sacrifice for the nation and state. Then it can beconcluded that the Copying Group has a role in raising awareness of the defense ofthe student state in East Java.